Future prospects of multi-level marketing in bangladesh - Akter, Aklima (Journal of Management and Science, 2013)
In this era of globalization of market place, marketing plays a significant role in every economy. Among the different dimensions of marketing, Multi-Level Marketing (MLM) is one of the crucial dimensions of marketing. This paper explores the concepts, affecting variables and future prospects of Multi-level Marketing in Bangladesh. The study is mainly based on both primary and secondary data. For conducting this research, 100 respondents were selected. The questionnaire consists of different questions were developed by using a five point Likert scale. The data obtained were analyzed using the SPSS software version-16.0. The result of this study indicates that there is a strong relationship between dependent variable and the independent variables. The correlation matrix shows that correlation is highly significant incase of corporate social responsibilities and Government rules and regulations. As the MLM industry has the opportunity for considerable growth, judging from the overseas experience. Thus, it is the proper time to formulate the legal and strategic policy issues for protecting the interest of people and regulating the MLM industry. Finally, an attempt has been made in this paper to enlist some recommendations.